Do we owe each other our emotional labor? - RAO, Aliya Hamid (Institutional Knowledge at Singapore Management University, 2015)
In academia our intellectual pursuits are also inherently emotional. It is thus unsurprising that in a recent blog post (here) another graduate student makes a case for acknowledging that academic work is infused with emotional labor, and for creating a space for “crying in academia.” She urges us to move away from scripts of professionalism so that we can stop pretending that emotional labor is not intrinsic to almost all that we do as aspiring academics.